PEMODELAN KONTINU 2-D BERBASIS EFEK ELEKTOKINETIK DENGAN FINITE ELEMENT PENDEKATAN GALERKIN - Delia Meldra (Universitas Putera Batam, 2019)
Method refers to a measurement of naturally electric potential on the surface. Self Potential is one of thegeophysical methods that can be used to identify fluid flow in the subsurface. Finite element method hasbeen used to fluid flow velocity modeling, current source, and potential distribution modeling based onelectrokinetic effect in 2-D profile. The sign of potensial respon (negative or positive) is an important factorfor the interpretation of self-potential anomalies. Finite element method is one of the numerical methods forsolve the boundary value problems and the boundary conditions in the form of differential equations in SelfPotentialmodeling